INTERNALISASI KARAKTER MELALUI TUJUH ADAGIUM SMPN 7 TASIKMALAYA - Abdul Palah (MGMP PAI Jawa Barat, 2023)
The purpose of conveying the seven adages of SMP Negeri 7 Tasikmalaya by each subject teacher is so that students unconsciously receive and store this advice in their subconscious so that it will make an impression so that in time it will appear reflexively without having to think about it again. As for the targets of this activity are teachers as implementation guides, students as actors of character internalization and guidance and counseling teachers as monitors of student character development. The implementation period is 6 months in the even semester of the 2021/2022 school year from January to July 2022, taking place at SMP Negeri 7 Tasikmalaya. The method of implementing the program for internalizing the character of students with adages/advice delivered by the subject teacher at the end of each lesson that has been carried out, this is a series of process activities carried out in a systematic and planned manner. Based on the results and discussion, it can be concluded that character internalization by conveying adages/advice at SMP Negeri 7 Tasikmalaya by each subject teacher at the end of learning is proven to be able to reduce student barriers, as evidenced by 45 students or 9.05%, who had learning barriers before a character internalization program was held by conveying the adage of SMP Negeri 7 Tasikmalaya which decreased to 18 students or 3.62%, there was a decrease, 27 students or 5.43%. after the character internalization program through the delivery of adages at SMP Negeri 7 Tasikmalaya, out of 30 students or 6.04% who had social barriers before the character internalization program was held through delivering adages at SMP Negeri 7 Tasikmalaya, it decreased to 11 students or 2.21% there was a decrease , 29 students or 3.83%. and of the 36 students or 7.24% who had personal barriers before the character internalization program was held through the delivery of the adage of SMP Negeri 7 Tasikmalaya it decreased to 12 students or 2.41% there was a decrease, 24 students or 4.83%. after the character internalization program by conveying the adage of SMP Negeri 7 Tasikmalaya